Formation and growth mechanisms of polycyclic aromatic hydrocarbons: A mini-review. (March 2022) - Reizer, Edina; Viskolcz, Béla; Fiser, Béla
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are mostly formed during the incomplete combustion of organic materials, but their importance and presence in materials science, and astrochemistry has also been proven. These carcinogenic persistent organic pollutants are essential in the formation of combustion generated particles as well. Due to their significant impact on the environment and human health, to understand the formation and growth of PAHs is essential. Therefore, the most important growth mechanisms are reviewed, and presented here from the past four decades (1981–2021) to initiate discussions from a new perspective. Although, the collected and analyzed observations are derived from both experimental, and computational studies, it is neither a systematic nor a comprehensive review. Nevertheless, the mechanisms were divided into three main categories, acetylene additions ( e.g. HACA), vinylacetylene additions (HAVA), and radical reactions, and discussed accordingly. Graphical abstract: Image 1 Highlights: All PAH growth mechanisms proposed between 1981 and 2021 were summarized. Three main categories of the mechanisms have been identified. Radical reactions, acetylene and vinylacetylene additions were presented.